Dekonstruksi Sosial dalam Novel Hikayat The Da Peci Code Karya Ben Sohib - Azril Azril; Noni Andriyani (UIR Press, 2022)
This study aims to describe the form of social deconstruction in the novel the da peci code saga by Ben Sohib. The approach used in this study is a qualitative approach, which produces descriptive data in the form of written or spoken words from the people and behaviors that the data observed. The theory used in this study uses Derrida's theory of deconstruction based on seven concepts of Grammatology, logocentrism, Difference, text terms, Phonocentrism, writing itself, dissemination. This research method uses descriptive method. The social criticism in this novel is a criticism that is common in everyday life, such as the habit of using a white cap which some people consider obligatory to be straightened out with the idea that the cap is just a symbol, the notion that maulid is a futile act is explained by the arguments in Surah Al -A'raf verse 157. This research method uses a descriptive method. The benefit of deconstruction in this novel is as a guide in being critical in everyday life.